Antimicrobial Resistance and Community Pharmacists' Perspective in Thailand: A Mixed Methods Survey Using Appreciative Inquiry Theory - Rojjares Netthong; Ros Kane; Keivan Ahmadi (MDPI AG, 2022)
Global action plans to tackle antimicrobial resistance (AMR) are the subject of ongoing discussion between experts. Community pharmacists have a professional responsibility to tackle AMR. This study aimed to evaluate the knowledge of antibiotic resistance and attitudes to promoting Antibiotic Smart Use (ASU) amongst part and full-time practicing community pharmacists across Thailand. An online mixed-method survey applying Appreciative Inquiry theory was validated and conducted in 2020. Non-probability sampling was used, with online survey dissemination via social networks. A total of 387 community pharmacists located in 59 out 77 provinces seemed knowledgeable about antimicrobial resistance (mean score = 82.69%) and had acceptable attitudes towards antibiotic prescribing practices and antimicrobial stewardship (mean score = 73.12%). Less than 13% of pharmacists had postgraduate degrees. Postgraduate education, training clerkship, preceptors, and antibiotic stewardship training positively affected their attitudes. The community pharmacists proposed solutions based on the Appreciative Inquiry theory to promote ASU practices. Among these were educational programmes consisting of professional conduct, social responsibility and business administration knowledge, up-to-date legislation, and substitutional strategies to compensate business income losses.